Stability Of A Generalized Alternate 3 Dimensional Additive Functional Equation In Various Banach Spaces - Sathya, E. (International Journal of Advanced Mathematical Sciences, 2024)
In this paper, the generalized Ulam – Gavruta stability of a generalized alternate 3 dimensional additive functional equation in various Banach spaces using Hyers method.